THE IMPACT OF DIGITAL MARKETING APPLICATIONS ON CONSUMER SATISFACTION AND BEHAVIOR IN EVENT MARKETING: A STUDY IN SOUTHEAST ASIA - Rozita Naina Mohamed; Anusara Sawangchai; Mohd Saifullah Rusli; J.S. Keshminder; S.C. Chuah; Wanchai Akpornpis (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
This study examines the impact of perceived effectiveness behavior on consumer satisfaction in using digital marketing applications in event marketing across Southeast Asia. By investigating key variables such as the learning environment, accessibility to event organizers, and the degree of app usage, the research aims to understand how these factors influence consumer satisfaction with the app’s functionalities. Data were collected from users across Southeast Asia who frequently engage with event marketing applications. The findings reveal that user-friendly learning environments, easy accessibility to businesses, and extensive app usage significantly enhance consumer satisfaction. These insights offer valuable implications for app developers and event marketers seeking to optimize digital tools for improved consumer engagement. Specifically, the results suggest that fostering perceived effectiveness behavior through creating intuitive learning resources, improving business accessibility via apps, and encouraging more comprehensive app usage can lead to higher levels of consumer satisfaction within the Southeast Asian event industry.